Immunomorphological assessment of regional lymph nodes for predicting metastases in oral squamous cell carcinoma - Satish T Yadav; G S Madhu Shankari; K Chatura; Rani J Dhanuja; M Rashmi (Wolters Kluwer Medknow Publications, 2012)
Background: Oral squamous cell carcinoma is the most common neoplasm and comprises of approximately 80% of the cancers occurring in the oral cavity. The role of the host response to this neoplasm has been recognized, and for many years the regional lymph node in tumor-bearing hosts has been considered as an anatomic barrier to the systematic dissemination of tumor cells. Morphological evaluation of the regional nodes has aided in understanding the immune response. Aim: The current study was carried out to observe the morphological changes occurring in the regional lymph nodes and to evaluate whether these features could be helpful in assessing the immunological status of the patient, and thereby, the prognosis of the patient. Materials and Methods: The study was based on lymph nodes from 63 patients with oral squamous cell carcinoma, who underwent radical neck dissection or modified neck dissection. In the lymph node, four morphological patterns were observed that included lymphocyte predominance, germinal center predominance, mixed pattern (sinus Histiocytosis), and an unstimulated pattern. The cases were then divided into four groups according to the predominant immunoreactivity pattern based on the World Health Organization (WHO) standardized system for reporting human lymph node morphology. Results: Revealed that risk of metastases to cervical lymph nodes in patients with lymphocyte predominance was less (28.6%) when compared to the high risk of metastases with germinal center predominance (68%), and these results were statistically significant (P < 0.05). Patients with a mixed pattern showed less risk of metastases (45.4%), while those with an unstimulated pattern had increased risk of metastases (66.6%), but the results were not statistically significant. It was also found that in the positive nodes, germinal center hyperplasia (50.2%) was the predominant pattern. Conclusion: The present study revealed that patients with lymphocyte predominance had less risk of metastases and patients with germinal center predominance had a high risk of metastases to the lymph node.